Aplikasi Interaktif Pengenalan Huruf Hijaiyah Sebagai Media Pembelajaran Anak - Linda Azka Dini; Sri Muryani; Khoirun Nisa (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Learning to Read the Koran is important for Muslims, learning the Koran is given as early as possible to children with the aim to more quickly study the Koran with tartil as well as to instill the values of Islamic religious education in the child. Before going to the Koran reading stage, the first thing to learn is the introduction of hijaiyah letters. Starting from the pronunciation and how to distinguish the forms, amounting to 30 letters. As the development of technology today, the interest in learning by the book method often makes children bored. So that researchers realize how important it is to introduce hijaiyah letters to children with a fun interactive application. This interactive application is expected to make it easier for children to learn to recognize hijaiyah letters. Its introduction uses audio animation, visuals, and games which are expected to be more effective and efficient than learning methods using books. It is hoped that children will be even more motivated in learning to recognize hijaiyah letters. Based on the results of interactive application testing the introduction of hijaiyah letters for children states that this application can run well on computers and many children love it